MRI-guided microwave ablation and albumin-bound paclitaxel for lung tumors: Initial experience - Shen, Xiaokang; Chen, TianMing; Liu, Nianlong; Yang, Bo; Feng, GuoDong; Yu, Pengcheng; Zhan, Chuanfei; Yin, Na; Wang, YuHuang; Huang, Bin; Chen, Shilin (Frontiers in Bioengineering and Biotechnology, 2022)
Magnetic resonance-guided microwave ablation (MRI-guided MWA) is a new, minimally invasive ablation method for cancer. This study sought to analyze the clinical value of MRI-guided MWA in non-small cell lung cancer (NSCLC). We compared the precision, efficiency, and clinical efficacy of treatment in patients who underwent MRI-guided MWA or computed tomography (CT)-guided microwave ablation (CT-guided MWA). Propensity score matching was used on the prospective cohort (MRI-MWA group, n = 45) and the retrospective observational cohort (CT-MWA group, n = 305). To evaluate the advantages and efficacy of MRI-guided MWA, data including the accuracy of needle placement, scan duration, ablation time, total operation time, length of hospital stay, progression-free survival (PFS), and overall survival (OS) were collected and compared between the two groups. The mean number of machine scans required to adjust the needle position was 7.62 ± 1.69 (range 4–12) for the MRI-MWA group and 9.64 ± 2.14 (range 5–16) for the CT-MWA group (p < 0.001). The mean time for antenna placement was comparable between the MRI and CT groups (54.41 ± 12.32 min and 53.03 ± 11.29 min, p = 0.607). The microwave ablation time of the two groups was significantly different (7.62 ± 2.65 min and 9.41 ± 2.86 min, p = 0.017), while the overall procedure time was comparable (91.28 ± 16.69 min vs. 93.41 ± 16.03 min, p = 0.568). The overall complication rate in the MRI-MWA group was significantly lower than in the CT-MWA group (12% vs. 51%, p = 0.185). The median time to progression was longer in the MRI-MWA group than in the CT-MWA group (11 months [95% CI 10.24–11.75] vs. 9 months [95% CI 8.00–9.99], p = 0.0003; hazard ratio 0.3690 [95% CI 0.2159–0.6306]). OS was comparable in both groups (MRI group 26.0 months [95% CI 25.022–26.978] vs. CT group 23.0 months [95% CI 18.646–27.354], p = 0.18). This study provides hitherto-undocumented evidence of the clinical effects of MRI-guided MWA on patients with NSCLC and determines the relative safety and efficiency of MRI- and CT-guided MWA.